Ancient refugia and present‐day habitat suitability of native laurophylls in Italy. (10th April 2019) - Alessi, Nicola; Těšitel, Jakub; Zerbe, Stefan; Spada, Francesco; Agrillo, Emiliano; Wellstein, Camilla
Abstract: Questions: European native laurophyllous species are interesting for their biogeography and evolutionary history, as well as for their responses to global changes. We identified Italian native laurophylls on the basis of morphology, biogeographical history and ecological niche to study whether these species are in equilibrium with the present‐day climate. Furthermore, we localized Quaternary refugia and areas of potential spread of native laurophylls using distribution patterns of realized and potential aggregations of native laurophylls, respectively. Location: Italy. Methods: We extracted data for 17 087 forest plots from a phytosociological database. Detrended Correspondence Analysis of these plots with overlay of climatic and environmental variables was performed to identify native laurophylls, i.e., evergreen broad‐leaved species of late Tertiary radiation, occupying a warm and humid niche. Potential ranges of laurophylls were calculated using Beals' index of sociological favourability. The realized/potential range‐size ratio was calculated for each single laurophyll to understand whether it is in equilibrium with the present‐day climate. Distribution patterns of realized and potential aggregations of laurophylls were mapped. Results: Ordination analysis provided a selection of 11 species as Italian native laurophylls. Most of them occupied less than half of their estimated potential range. Realized aggregations richest in native laurophylls were localized in the central Apennines. However, the Italian forests showed high potential for native laurophylls with the richest potential aggregations in the whole Apennines and in the southern Alps. Conclusions: Most of the Italian native laurophylls showed non‐equilibrium with the current climate, suggesting that late‐Quaternary events could better explain their present‐day distribution than on‐going climate change. Furthermore, their refugia in central Italy suggest the persistence in sites with temperate climate during Quaternary environmental changes. The high suitability of Italian forests for laurophylls, along with global changes, suggests possible future spreading of these species. Abstract : European native laurophylls are well‐known for their biogeography, evolutionary history, and global‐change responses. We identified Italian native laurophylls based on their morphology, biogeographical history and ecology. We found that their current distribution is not in equilibrium with climate but it represents past refugia. The high suitability of Italian forests for laurophylls, along with global changes, suggests possible future spreading.